ASPERGILLOMA PADA TUBERKULOSIS PARU: LITERATURE REVIEW - Arianto, Wily; Lasmaria, Rohani (Poltekkes Kemenkes Bandung, 2024)
Indonesia ranking among the top six countries with the highest TB burden. In the aftermath of pulmonary TB, fungal infections, particularly those caused by Aspergillus species, have emerged as a notable complication. The predominant species, Aspergillus fumigatus, is responsible for a spectrum of conditions ranging from invasive to noninvasive aspergillosis. This literature review aims to provide an exhaustive analysis of post-TB pulmonary aspergilloma, a clinical condition characterized by the growth of Aspergillus fungal balls within pre-existing lung cavities. Utilizing databases such as PubMed, Science Direct, EBSCO, Emerald, Scopus, and Google Scholar, and employing keywords such as